Efeito da alteração do hábitat sobre assembleias de peixes em igarapés afogados da Amazônia oriental - SOUSA, Híngara Leão (Universidade Federal do Pará, 2014)
The natural aquatic ecosystems are complex systems that are exposed to a variety of disturbances. In the Amazon region, for instance, land use and occupation have altered the physical structure of aquatic environments, especially regarding the small streams, influencing their communit structure and composition. This has led to research development and evaluation programs to see how the changes that are occurring in these environments affect biotic communities, through habitat characteristics that are more sensitive to disturbance. Thus, this study aimed to describe and measure physical attributes of drowned out streams and evaluate how fish assemblages respond to different levels of streams physical integrity. Our hypothesis is that structurally intact environments endure a more diverse ichthyofauna than altered environments, since their decreased environmental complexity limits the potential ecosystem, because they presented a decrease in environmental complexity. The study was conducted in 34 streams, 17 located within the territory of Caxiuanã National Forest, and 17 in its surroundings, located close to Portel and Melgaço cities (PA). The process of urbanization is expanding in the region, reaching areas of forests and streams that are still preserved. There is also an intense logging, because the area is included in the main timber pole of the estuary in the state of Pará. The physical habitat was evaluated according to a standardized protocol of stream environmental assessment. The samplings were conducted with hand nets passed along 150 meter long reaches during six hours (divided among segments and collectors). Although a set of metrics which responded to the local impact gradient has been detected these were not sufficient to reduce or increase the number of species across different levels of preservation, maintaining substantially constant the wealth and abundance for all three groups (altered, intermediate and preserved). However, the difference was significant for the composition, with eleven exclusive exclusive species of altered habitats and eight preserved environments. The degradation of the physical environment, even at smaller scales favors the occurrence and abundance of most tolerant species and phenotypic plasticity, in addition to the population increase of opportunistic species. Different effects can be exerted on the groups of species that make up a community, since they have different biological and ecological attributes that include your answers to the same ecological variables. Therefore, the possible deconstruction of community groups of species (taxonomic, functional, etc.) may show different responses to the changes of habitat, being a promising strategy for linking environmental standards of richness characteristics displayed by these communities. Assessment of biotic integrity is also an alternative to identify effects of habitat alteration on species, especially considering the region’s peculiarity and the lack of information about the local ichthyofauna.